Implementação da técnica citológica (imprint) para diagnóstico da esporotricose felina no município de Ribeirão das Neves - MG - Keterlly Silva Mota de Souza (2022)
Sporotrichosis is a subcutaneous mycosis that affects humans and animals, acquired by traumatic inoculation through plant material and soil contaminated with pathogenic species of the genus Sporothrix spp. or by bites and scratches of an animal infected by the fungus. Initially was an occupational disease but currently is an emerging and neglected zoonotic disease, resulting in epidemics with a serious public health problem. The participation of the feline in the route of transmission of the disease has caused an increase in the number of cases due to the domestic coexistence of humans and domestic cats. The municipality of Ribeirão das Neves in Minas Gerais had its first zoonotic case recorded in 2017. Since then, several cases of felines with suspected sporotrichosis have been found in the aforementioned municipality. The importance of a quick and viable diagnosis in public health units, which complements the veterinary clinical evaluation, favors the treatment of these animals, reducing the risk of zoonotic transmission and epizootics and consequently interfering with the dissemination of the disease. The present study aims to evaluate the accuracy and reliability of the cytopathological method using rapid panoptic dye in the diagnosis of feline sporotrichosis to obtain a quick result. It is vital to begin treatment as soon as possible and to promote social control measures. The results indicate that the cytological method is effective to display yeast cells of the characteristics of the genus Sporothrix. This study contributed to demonstrate that the cytological technique favors the rapid diagnosis of feline sporotrichosis in order to start treatment early, preventing the spread of the disease, reducing animal abandonment and the number of euthanasias in the Zoonosis Control Centers, helping professionals of health in the identification of the disease, in addition to reducing costs and impacts on the public health of the municipality.